THE USE OF AUDIO TRIMMER AS AN ONLINE APPLICATION TO IMPROVE STUDENTS' ABILITY IN ENGLISH LISTENING CLASS - Rina Herlina; Etika Rachmawati; Bambang Ruby Sugiarto (JALL (Journal of Applied Linguistics and Literacy), 2022)
This study focuses on the use of an online application-based Audio Trimmer in learning Listening in the English study program. The aim is to find out how the lecturer applies this Audio Trimmer application to Listening class and to find out the level of student satisfaction with the use of Audio Trimmer in Listening learning. Audio Trimmer is an online application that can adjust the audio tempo. So, no matter how difficult listening is, it will be resolved by using this application. Audio Trimmer has indeed been used as a learning medium in the Listening course for two semesters and there are indicators of student satisfaction with the use of the application. Therefore, this research is qualitatively designed with a case study approach with the research subject being all students from two listening classes, namely Extensive Listening and Academic Listening, and the data collection was obtained from student questionnaires in the form of a Likert scale questionnaire in the form of ten statements, class observation, and documentation of student achievements in listening courses. Then the research analysis includes data reduction, data display, and data verification. There are two findings from this study. First, the audio trimmer is used in listening courses at the whilst-activity and post-activity stages. Second, the student's perception shows that the audio trimmer is very supportive of listening learning. In conclusion, the audio trimmer in learning listening is very useful and of course highly recommended for English learners who will listen to English audio.